2012
DOI: 10.1074/jbc.m112.350397
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Cellular Localization and Function of Checkpoint Kinase 1 (Chk1) in Checkpoints and Cell Viability

Abstract: Background: Chk1 regulates both nuclear and cytoplasmic checkpoints. Results: The Chk1 polypeptide contains mechanisms mediating its cellular localization. Conclusion: The nuclear (but not cytoplasmic) pool of Chk1 is essential for cell viability. Significance: Dissecting mechanisms regulating the mobilization of Chk1 within different cellular compartments is critical for understanding checkpoint activation and its roles in cell biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 29 publications
5
42
2
Order By: Relevance
“…S6A). This observation is in conflict with the observations made by other groups, for example, Wang et al (31), with ectopically expressed CHK1 that showed persistent nuclear localization. We speculate that the discrepancy may result from the difference between endogenous CHK1 and ectopically expressed protein and also in the level of expression for the latter, as we also observed in HA-CHK1-transfected cells that cells expressing higher levels of CHK1 tend to retain the protein in the nucleus.…”
Section: Cdt2contrasting
confidence: 94%
“…S6A). This observation is in conflict with the observations made by other groups, for example, Wang et al (31), with ectopically expressed CHK1 that showed persistent nuclear localization. We speculate that the discrepancy may result from the difference between endogenous CHK1 and ectopically expressed protein and also in the level of expression for the latter, as we also observed in HA-CHK1-transfected cells that cells expressing higher levels of CHK1 tend to retain the protein in the nucleus.…”
Section: Cdt2contrasting
confidence: 94%
“…Previous studies have suggested that even though the cytoplasmic pool of CHK1 is important for checkpoint function, it is the nuclear pool of CHK1 that supports cell viability,36 which does not directly support our observations in VSCC. However, few reports have implicated CHK1 in apoptosis via CHK1‐mediated phosphorylation of p73 at Ser47, resulting in a strong increase in p73 transcription activity in response to DNA damage 37.…”
Section: Discussioncontrasting
confidence: 99%
“…43 Recent mouse work supports an impact of Mcph1 deficiency on centrosomal Chk1, suggesting that pericentrin may affect Chk1 at the centrosome. 36 If the key controls on Chk1 depend on its activation through a nuclear-cytosolic/centrosomal feedback loop, 44 localization of even a small fraction of Chk1 within the PCM may be a mechanism by which Mcph1 and pericentrin determine its interactions with its regulators.…”
Section: Discussionmentioning
confidence: 99%